Auto-Immune Glial Fibrillary Acidic Protein Astrocytopathy with Active Intrathecal Epstein-Barr Virus: A Single-Center Case Series Report - Yu X; Zou Y; Li M; Wang L; Feng W; Wei L; Yang L; He J; Bu H; Li Y (Neuropsychiatric Disease and Treatment, 2025)
Xiujun Yu,1,* Yueli Zou,1,* Man Li,1 Liqing Wang,1 Wenfeng Feng,2 Lingge Wei,3 Lan Yang,3 Junying He,1 Hui Bu,1 Yi Li1 1Department of Neurology, The Second Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China; 2Department of Radiology, The Second Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China; 3Department of Nuclear Medicine, The Third Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Li, Department of Neurology, The Second Hospital of Hebei Medical University, No. 215, Heping West Road, Shijiazhuang City, Hebei Province, People’s Republic of China, Email liyi_1106@163.com Hui Bu, Department of Neurology, The Second Hospital of Hebei Medical University, No. 215, Heping West Road, Shijiazhuang City, Hebei Province, People’s Republic of China, Email 869175930@qq.comPurpose: Auto-immune glial fibrillary acidic protein (GFAP) astrocytopathy is a disease with unclear mechanisms and no diagnostic and treatment guidelines. Epstein-Barr virus (EBV) infection is reportedly involved in glial activities. However, the relationship between GFAP astrocytopathy and EBV infection is not clear. This study reports a case series of auto-immune GFAP astrocytosis with positive cerebrospinal fluid (CSF) EBV DNA, describing its clinical manifestations and treatment experience.Patients and Methods: In the serial case study, we reported six patients diagnosed with GFAP astrocytopathy having intrathecal EBV.Results: The significant signs included headache, fever and urination disorder, ataxia, limb weakness, numbness, consciousness disorder, psychological disorder, and blindness, among others. CSF analysis showed increased pressure, white blood cell count, abnormal biochemical components, positive GFAP antibody, and EBV. The positive results of metagenomic next-generation sequencing (mNGS) and PCR in CSF indicated that there might be active replication of EBV in the CSF of patients. The results of EBV-associated antibodies in blood suggest no evidence of acute primary EBV infection in six patients. Initial single antivirus therapy did not show satisfactory effects, but all patients showed improvement in clinical features and laboratory analysis after immunotherapy.Conclusion: This study indicated that intrathecal EBV activity was closely related to auto-immune GFAP astrocytopathy, of which the mechanism remains to be further studied.Keywords: autoimmune GFAP astrocytopathy, Epstein-Barr (EB) virus, cerebrospinal fluid, glial fibrillary acidic protein, next-generation sequencing, MRI